Précisez l'ensemble de définition de la fonction indiquée et calculez sa dérivée.

Ex 65:

a) f:x-> [(e^x)/2] * (x²-1) b) f:x->(e^x + 2)/(1-e^x)

Ex 66:

a) f:x-> racine de x + 3e^x b)f:x-> [x(1-e^x)]/e^x

Ex 67:

a) f:x-> e^x*racine de 1-x b) f:x-> e^x * racine de x

1

Réponses

  • Utilisateur Brainly
2012-11-27T21:21:57+01:00

a Df=R dérivée (e^x/2)(2x+x²-1)

b Df=R* dérivée 3e^x/(1-e^x)²

c Df x>x0 ou x0 est LA solution de x+3e^x=0

 dérivée (1+3e^x)/2(racine(x+3e^x))

d Df=R dérivée(1-x-e^x)/(e^x)

 

e Df= x<1 dérivée e^x(rac(1-x)-1/2rac(1-x))

 

f Df=R+ dérivée e^x(rac(x)+1/2rac(x))